Analisis Penerapan Sistem Manajemen Pendidikan Tinggi Untuk Mewujudkan Good University Governance - Rispa Ngindana; Langgeng Rachmatullah Putra; Rinaldo Albertus (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2020)
The implementation of higher education management system in public universities is not new anymore, but every challenge of innovation developed has always been a new problem for college maintainers. This research aims to analyse the implementation of education management system, and control system of educational system of education in higher education environment, especially State University and developing alternative model of coordination system in implementing higher education management system. The research methods used are qualitative research with case study approaches. The research location is determined based on purposive sample method. The results of the study showed that control system in implementing the management system of higher education in Brawijaya University involves several systems and actions as follows: 1) quality assurance system; 2) work properly; 3) Customer satisfaction guarantee; 4) Pay attention to and record stakeholders ' complaints; 5) management based on facts; 6) Continuous improvement.